6‐phenylpyrrolocytosine as a fluorescent probe to examine nucleotide flipping catalyzed by a DNA repair protein. Issue 1 (24th October 2020) - Kotandeniya, Delshanee; Rogers, Melanie S.; Fernandez, Jenna; Kanugula, Sreenivas; Hudson, Robert H. E.; Rodriguez, Freddys; Lipscomb, John D.; Tretyakova, Natalia
Abstract: Cellular exposure to tobacco‐specific nitrosamines causes formation of promutagenic O 6 ‐[4‐oxo‐4‐(3‐pyridyl)but‐1‐yl]guanine ( O 6 ‐POB‐G) and O 6 ‐methylguanine ( O 6 ‐Me‐G) adducts in DNA. These adducts can be directly repaired by O 6 ‐alkylguanine‐DNA alkyltransferase (AGT). Repair begins by flipping the damaged base out of the DNA helix. AGT binding and base‐flipping have been previously studied using pyrrolocytosine as a fluorescent probe paired to the O 6 ‐alkylguanine lesion, but low fluorescence yield limited the resolution of steps in the repair process. Here, we utilize the highly fluorescent 6‐phenylpyrrolo‐2′‐deoxycytidine (6‐phenylpyrrolo‐C) to investigate AGT‐DNA interactions. Synthetic oligodeoxynucleotide duplexes containing O 6 ‐POB‐G and O 6 ‐Me‐G adducts were placed within the CpG sites of codons 158, 245, and 248 of the p53 tumor suppressor gene and base‐paired to 6‐phenylpyrrolo‐C in the opposite strand. Neighboring cytosine was either unmethylated or methylated. Stopped‐flow fluorescence measurements were performed by mixing the DNA duplexes with C145A or R128G AGT variants. We observe a rapid, two‐step, nearly irreversible binding of AGT to DNA followed by two slower steps, one of which is base‐flipping. Placing 5‐methylcytosine immediately 5′ to the alkylated guanosine causes a reduction in rate constant of nucleotide flipping. O 6 ‐POB‐G at codon 158 decreased the base flipping rate constant by 3.5‐fold compared with O 6 ‐Me‐G at the same position. A similar effect was not observed at other codons. Abstract :